Hippocampus patagonicus - Jasmine, Wei (2017)
Hippocampus patagonicus is a coastal species of seahorse that inhabits waters from northeastern Brazil to Chubut, Argentina. The major habitats occupied by the species include seagrasses, macroalgae, and sheltered areas with sessile invertabrates. The species is threatened by habitat degradation and loss from coastal development and destructive fishing practices, targeted exploitation, and by being caught extensively as bycatch in shrimp trawl fisheries. Based on declining habitat quality, extent of occurrence, and declines reported by fishers, it is inferred that the population has undergone a decline of at least 30%. Therefore Hippocampus patagonicus is listed as Vulnerable under criterion A2cd.